Cyprian Norwid and the History of Greece - Junkiert, Maciej (Studies in Classical Literature and Culture, 2020)
Ancient Greek history holds a special place in the works of many 19th-c. writers. The same goes for Cyprian Norwid, one of the most eminent poets in the history of Polish literature, a thinker, and an artist. This book scrutinizes Norwid's fascination with Greek history and culture, especially his peculiar synthesis of Greek thought and Christianity. It focuses on the key themes of the relationship of Platonism with early Christian writings and their presence in Norwid's contemporary culture, the opposition of memory and history in 19th-c. literature and social life, and the image of the artist and its influence on social life in modern everyday. The book analyzes Norwid's oeuvre in a broad comparison with representatives of French, German, and British literature and the humanities.